2002
DOI: 10.1063/1.1488241
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical, and optical properties of defects in Si-doped GaN grown by molecular-beam epitaxy on hydride vapor phase epitaxy GaN on sapphire

Abstract: Molecular-beam epitaxy (MBE) has been utilized to grow Si-doped GaN layers on GaN/sapphire templates prepared by hydride vapor phase epitaxy. An extensive set of characterization techniques is applied to investigate the layers. Positron annihilation experiments indicate that the samples contain open volume defects, most likely clusters of vacancies and possibly Ga vacancy-donor complexes. The number of vacancy clusters decreases, as Si concentration is increased. Photoluminescence spectra show that while the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The (S, W) points fall clearly off the line characteristic of the Ga vacancy (V Ga -O N complex) identified earlier [18,19]. On the other hand, the data fits well with the line previously associated to vacancy clusters formed in MBE grown GaN samples [20,21]. Instead of simple point defects like V Ga and V Ga -O N , the MT region thus contains empty vacancy clusters where several Ga and N atoms are missing.…”
Section: Native-related Defectssupporting
confidence: 70%
See 1 more Smart Citation
“…The (S, W) points fall clearly off the line characteristic of the Ga vacancy (V Ga -O N complex) identified earlier [18,19]. On the other hand, the data fits well with the line previously associated to vacancy clusters formed in MBE grown GaN samples [20,21]. Instead of simple point defects like V Ga and V Ga -O N , the MT region thus contains empty vacancy clusters where several Ga and N atoms are missing.…”
Section: Native-related Defectssupporting
confidence: 70%
“…In addition, we recorded RS spectra (not shown here) taken in several spots circularly arranged around a barrier stripe in order to check for in-plane distribution of the strain in the MT areas. No shift of the E 2 mode [20,21]) are also shown. was observed, showing a homogeneous strain distribution.…”
Section: Strain Distributionsmentioning
confidence: 91%
“…The ratio is minimum when buffer layer thickness are 30 and 20 nm for samples grown on SP substrate and DP substrate, respectively. Generally it is thought that the YL relates to point defects, such as V Ga ; V Ga -related compounds and other impurities [25,26]. Theoretical calculation indicated that dislocations in GaN acted as acceptors and perhaps related to the source of YL [27,28].…”
Section: Samplementioning
confidence: 98%
“…For all the samples, the S parameters first decrease rapidly at low energy, which results from positron annihilations and formation of positronium atoms at sample surface. 15 As the positron implantation energy increased, fewer positrons are able to diffuse to the sample surface. At 3 -20 keV the S parameter becomes approximately constant indicating almost all positrons are annihilated in the bulk layer.…”
mentioning
confidence: 99%